Peningkatan Kualitas Bokar Petani Karet Desa Lorok, Ogan Ilir: Improving the Quality of Rubber Farmers in Lorok Village, Ogan Ilir - Bakri, Bakri; Meilasari, Nabilla; Paserena, Karinda Dwi; Leviana, Leviana; Ma'shum, Halim; Sari, Shabilla Amartiya (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This Community Service Activity aims to improve the quality of rubber farmers' bokar in Lorok Village, Ogan Ilir, through effective tapping techniques, controlling white root fungus with Trichoderma sp, and using recommended coagulants. The implementation took place from September to December 2025 in Lorok Village, Ogan Ilir. The targets are for rubber farmers, rubber collectors, and Lorok Village officials. The activity began with a Forum Group Discussion and interviews to identify the problems of rubber farmers in Lorok Village, then preparing socialization materials, training and coaching designs, as well as pre- and post-activity evaluations; socialization, demonstrations, and mentoring; and analyzing Bokar results as an evaluation of the implementation of efforts to improve the quality of Bokar that were socialized. From the results of the activity, it was found that rubber farmers in Lorok Village can produce high-quality bokar if they apply effective tapping techniques, select recommended coagulants, and control JAP with Trichoderma sp. By carrying out this activity, farmers believe they will be able to increase their income by selling high-quality bokar at competitive selling prices for industrial needs.